Raman spectra and electron microscopic investigations of the sections of modified As₂S₃ glasses - Mateleshko, N.; Mitsa, V.; Borkach, E. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
Chalcogenide vitreous semiconductors (ChVS) are used as memory elements, elements of fiber, integral and power optics [1–6]. The change of the synthesis conditions results in the change of structure and, as a consequence, physical parameters of ChVS [1]. It means that it is possible to find solution of the fabrication of glasses with high optical strength by using modification of ChVS structure [2]. The objective of the present work is to investigate the influence of the temperature-temporal conditions of the fabrication on the structure of As₂S₃ glasses by the method of the Raman scattering spectroscopy and electron microscopy and also to choose the conditions of fabrication of As₂S₃ glasses with the continuously bonded matrix of the structure suitable for power optics using this basis.